Prognosis of silent atrial fibrillation after acute myocardial infarction at 1-year follow-up - Stamboul, Karim; Zeller, Marianne; Fauchier, Laurent; Gudjoncik, Aurélie; Buffet, Philippe; Garnier, Fabien; Guenancia, Charles; Lorgis, Luc; Beer, Jean Claude; Touzery, Claude; Cottin, Yves (Heart (British Cardiac Society), 2015)
Background Silent atrial fibrillation (AF), assessed by continuous ECG monitoring (CEM), has recently been shown to be common in acute myocardial infarction (AMI), and associated with higher hospital mortality. However, the long-term prognosis is still unknown. We aimed to assess 1-year prognosis in patients experiencing silent AF in AMI. Methods All consecutive patients with AMI who were prospectively analysed by CEM during the first 48 h after admission and who survived at hospital discharge were included. Silent AF was defined as asymptomatic episodes lasting at least 30 s. Patients were followed up at 1 year for cardiovascular (CV) outcomes. Results Among the 737 patients analysed, 106 (14%) developed silent AF and 32 (4%) symptomatic AF. Compared with the no-AF group, patients with silent AF were markedly older (79 vs 62 years, p<0.001), more frequently hypertensive (71% vs 49%, p<0.001) and less likely to be smokers (23% vs 37%, p<0.001). Also, they were more likely to have impaired LVEF (50% vs 55%, p<0.001). Risk factors in patients with silent AF were similar to those in patients with symptomatic AF. However, a history of stroke or AF was less frequent in silent AF than in symptomatic-AF patients (10% vs 25% and 10% vs 38%, respectively). At 1 year, CV events including hospitalisation for heart failure (HF) and CV mortality were markedly higher in silent-AF patients than in no-AF patients (6.6% vs 1.3% and 5.7% vs 2.0%, p<0.001, respectively). Conclusions Our large prospective study showed for the first time that silent AF is associated with worse 1-year prognosis after AMI. Systematic screening and specific management should be investigated in order to improve outcomes of patients after AMI.